An ethnobotanical study on medicinal plants of Shexian Dryland Stone Terraced System in northern China - Yu Bai; Qing Zhang; Xianlin He; Haifei Wang; Wanlin Li; Jinfeng Zhu; Yuan Meng; Chunlin Long (BMC, 2022)
Abstract Background Shexian Dryland Stone Terraced System (SDSTS) in the Taihang Mountains was formally recognized as Globally Important Agricultural Heritage Systems (GIAHS) by Food and Agriculture Organization on May 20, 2022. People there have been relying on the terraced fields for centuries, using various plants, including medicinal plants. However, little information was reported about the flora in SDSTS, nor medicinal plants. Thus, the present study aims to identify and document medicinal plants traditionally used by the local people living around the SDSTS and associated ethnobotanical knowledge. Methods We conducted investigations in Shexian County, Hebei Province, North China, where SDSTS is distributed. Then, Wangjinzhuang, a community located in the core zone of SDSTS, was chosen as the case site. We selected the informants through purposive and snowball sampling. The data were collected through semi-structured interviews, participant observation, and key informant interviews. The medicinal plants traditionally used by the local people were documented and analyzed. We examined and confirmed the botanical identification based on voucher specimens and by cross-checking the descriptions with the series of books, scientific papers on medicinal plants, and the plant databases. Results The local people have rich traditional knowledge to collect and use medicinal plants in SDSTS. Records of 123 medicinal plant species belonging to 51 families were obtained from SDSTS. Asteraceae was represented by 16 species, followed by Fabaceae, Lamiaceae and Ranunculaceae. (They all have 8 species.) The majority of the reported plant species were commonly processed into decoctions. And 180 diseases affecting humans were reported to be treated with traditional medicinal plants from SDSTS. Conclusion It is the first ethnobotanical study on medicinal plants in China-Nationally Important Agricultural Heritage Systems, and in globally important agricultural heritage systems as well. Medicinal plants are crucial for people living in Shexian County. It is necessary to recognize and respect traditional knowledge peculiar to the mountainous region of northern China, especially for those involved in the human-nature interaction and the role of knowledge in agrobiodiversity conservation and rural development that local residents have persisted for centuries.